Politik Ekonomi Islam (Analisis Kebijakan Pembangunan Ekonomi dan Penentuan Anggaran Belanja Negara) - Hasan, Nurul Fatma; Amin, Moh. (Proceedings of Annual Conference for Muslim Scholars, 2019)
This article is written to analyze the Islamic politics of economy, namely governmental policy in developing economy and determining state budget. Islam, as a rah}mah li al-‘a>lami>n, rules everything, including determining the policy of economy. The objective of Islamic economy is in accordance with the main objective of the existance of Islam itself, namely to present the welfare for all human being here and here after. To reach the objective, reconstruction shall be done towards strategic elements, specifically the existance of filter mechanism emphasized to moral filter, the human motivation to prioritized social interest, the existance of socio-economy restructuring, and active role government in economy. To realize all those, the policy which shall be executed by government is to raise up humanity factor, reduce wealth concentration, restructure economy, restructure finance, and realize strategic policy plan oriented to the welfare of all human being. In determining state budget, government shall consider maqa>s}id al-shari>’ah principle which fulfills five hierarchies of basic need which must be fulfilled and protected, namely religion (di>n), soul (nafs), mind (‘aql), descendant (nasl), dan treasure (ma>l) protection